GAMBARAN FAKTOR INDIKASI PASIEN OPERASI SECTIO CAESAREA DI RUMAH SAKIT KHUSUS DAERAH IBUDAN ANAK PERTIWI MAKASSAR - asmah asmah (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2018)
Objective: to see the description of patient indication indication sectio casarea at Special Hospital Area Mother and Child of Makassar. Method: In this study descriptive use aims to get an accurate picture of a number of characteristics of the problems studied. The sample size in this study were 52 respondents who fit the inclusion criteria. The data were collected by using questionnaires. Results: The results showed that the age of patients sectio cesarea as much as 46.2% of high risk, and 53.8% of low risk. Fetal abnormalities as much as 67.3% good and 32.7% less. Early rupture of membranes as many as 40.4% and 59.6% who did not experience, History of severe disease 36.6% experienced, and as many as 65.4 who did not experience. Social economy as much as 67,3% and as much as 32,7%. Conclusion: The conclusion in this study is that the average indication factor mostly looks good. Suggestions: The results of this study can be used as information for the Maternal Special Hospital of Motherland and Children of Makassar in terms of more clarify about the determination of the type of labor